2016
DOI: 10.1186/s12864-016-2628-z
|View full text |Cite
|
Sign up to set email alerts
|

A high density genetic map and QTL for agronomic and yield traits in Foxtail millet [Setaria italica (L.) P. Beauv.]

Abstract: BackgroundFoxtail millet [Setaria italica (L.) P. Beauv.], a crop of historical importance in China, has been adopted as a model crop for studying C-4 photosynthesis, stress biology and biofuel traits. Construction of a high density genetic map and identification of stable quantitative trait loci (QTL) lay the foundation for marker-assisted selection for agronomic traits and yield improvement.ResultA total of 10598 SSR markers were developed according to the reference genome sequence of foxtail millet cultivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 35 publications
1
57
0
Order By: Relevance
“…Recently, Chinese scientists have reported the successful development of new elite varieties in rice by pyramiding major genes that significantly contribute to grain quality and yield from three parents over 5 years, and demonstrated that rational design is a powerful strategy for meeting the challenges of future crop breeding [58]. In foxtail millet, QTLs controlling agronomic traits have been detected in previous studies [16, 22, 23, 30]. Wang et al [23] and Fang et al [16] reported QTLs for PH, MPL, MPD, PWP, and GWP, using F 2 populations and SSR markers.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Chinese scientists have reported the successful development of new elite varieties in rice by pyramiding major genes that significantly contribute to grain quality and yield from three parents over 5 years, and demonstrated that rational design is a powerful strategy for meeting the challenges of future crop breeding [58]. In foxtail millet, QTLs controlling agronomic traits have been detected in previous studies [16, 22, 23, 30]. Wang et al [23] and Fang et al [16] reported QTLs for PH, MPL, MPD, PWP, and GWP, using F 2 populations and SSR markers.…”
Section: Resultsmentioning
confidence: 99%
“…All above results indicated that, those three agronomic traits present a wide range of changes and good selection effect. [12] One-Way Analysis of Variance (ANOVA) of the six agronomic traits of the 18 samples was performed with SPSS 16.0 to check whether the data of six agronomic traits were significantly different among different groups. A significance level of P < 0.05 was set.…”
Section: Characterization Cluster Analysis and Correlation Analysismentioning
confidence: 99%
“…Although many quantitative trait loci (QTLs) have been identified for various agronomic traits such as plant height, flowering time, lodging, and drought tolerance (Mauro-Herrera et al, 2013; Parvathaneni et al, 2013; Sato et al, 2013; Babu et al, 2014; Qie et al, 2014; Mauro-Herrera and Doust, 2016; Rajput et al, 2016), the QTL intervals are often large (>1 Mb) and difficult to fine map. A partial solution is to generate high density linkage maps using technologies like genotyping by sequencing (Moumouni et al, 2015; Fang et al, 2016; Rajput et al, 2016), but the ultimate solution is to build high-quality reference genomes. To date, foxtail millet remains the only millet that has a chromosomal scale genome assembly (Bennetzen et al, 2012; Zhang et al, 2012), while Eragrostis tef has a draft genome (Cannarozzi et al, 2014), and the genome sequencing of finger millet and pearl millets are still ongoing ( Table 1 ).…”
Section: Advances Of Forward Genetics In Setaria and Other Milletsmentioning
confidence: 99%
“…To date, foxtail millet remains the only millet that has a chromosomal scale genome assembly (Bennetzen et al, 2012; Zhang et al, 2012), while Eragrostis tef has a draft genome (Cannarozzi et al, 2014), and the genome sequencing of finger millet and pearl millets are still ongoing ( Table 1 ). Complete genome sequencing not only enables high density maps (Fang et al, 2016), but also large scale genome wide association studies (GWAS; Jia et al, 2013). Recently, a pre-publication release of an S. viridis genome de novo assembly became available through phytozome 1 .…”
Section: Advances Of Forward Genetics In Setaria and Other Milletsmentioning
confidence: 99%